Yogurt inhibits intestinal barrier dysfunction in Caco-2 cells by increasing tight junctions. Issue 1 (16th January 2017) - Putt, Kelley K.; Pei, Ruisong; White, Heather M.; Bolling, Bradley W.
Abstract : Yogurt improves inflammation-disrupted intestinal barrier function in differentiated Caco-2 cells. Abstract : Chronic inflammation disrupts intestinal barrier function and may contribute to the pathology of obesity and other diseases. The goal of this study was to determine the mechanism by which yogurt improves intestinal barrier function. Caco-2 cells were differentiated on Transwell inserts and used as a model of intestinal barrier permeability. Transepithelial electrical resistance (TEER) and flux of 4 kDa fluorescein isothiocyanate-dextran (FD) and lucifer yellow (LY) were used as indicators of monolayer integrity and paracellular permeability. Immunofluorescence microscopy and real time quantitative polymerase chain were used to assess the localization and expression of tight junction proteins known to regulate intestinal permeability. Differentiated cells were treated with a vehicle control (C), inflammatory stimulus (I) (interleukin-1β, tumor necrosis factor-α, interferon-γ, and lipopolysaccharide), or I and 0.03 g mL −1 yogurt (IY). After 48 h, I reduced Caco-2 TEER by 46%, while IY reduced TEER by only 27% ( P < 0.0001). FD and LY flux reflected TEER measurements, with IY having significantly lower permeability than I ( P < 0.05). Yogurt also improved localization of occludin and zona occludens protein 1 (ZO-1) at tight junctions of differentiated Caco-2 cells. IY increased Caco-2 claudin-1, ZO-1, and occludin mRNA relative to I ( P < 0.05). In a simulated digestion, the barrier-improving bioactivity of yogurt was maintained through the gastric phase, but was reduced to the level of I after intestinal digestion ( P < 0.05). Therefore, yogurt improved inflammation-disrupted intestinal barrier function in a Caco-2 model by increasing tight junctions, but the beneficial effect on barrier function was reduced at latter stages of digestion.